INSECT PEST COMPLEX AND CROP LOSSES IN PIGEON PEA IN MEDIUM ALTITUDE HILL OF MEGHALAYA - PATRA, SANDIP; FIRAKE, D. M; THAKUR, N. S. AZAD (The Bioscan, 2016)
Field experiments were carried out at ICAR Research Complex for North Eastern Hill Region, Umiam, Meghalaya to study the pest complex and crop losses in pigeon pea (Var: Bahar) during 2009-10 and 2010-11. Weekly observation was taken through Plant Inspection Method (PIM) from 30 plants since seedling stage to till maturity of the crop. Total 41 insect species comprising 11 Coleoptera, 13 Hemiptera, 3 Orthoptera, 1 Diptera, 1 Thysanoptera, 11 Lepidoptera and 1 Hymenoptera were recorded. Several natural enemies including 8 coccinellid beetles, 1 yellow wasp, 1 predatory bug and 2 unidentified parasitoids and some spiders were recorded during the crop seasons. Pod damage caused by different insect pests were recorded 8.75 and 6.25% by Helicoverpa armigera, 7.50 and 5.25% by Lampides boeticus, 31.25 and 67.5% by Apion clavipes and 44.94 and 17.75% by Melanagromyza obtusa during first and second seasons, respectively. Mean pod damage caused by H. armigera, L. boeticus, A. clavipes and M. obtusa were found to be 7.50, 6.38, 49.38 and 31.35%, respectively. Results revealed that pod boring insects (H. armigera, L. boeticus, A. clavipes and M. obtusa) caused major crop losses to pigeon pea in this region.